Fine Mapping and Evolution of the Major Sex Determining Region in Turbot (Scophthalmus maximus). Issue 10 (1st October 2014) - Taboada, Xoana; Hermida, Miguel; Pardo, Belén G; Vera, Manuel; Piferrer, Francesc; Viñas, Ana; Bouza, Carmen; Martínez, Paulino
Abstract: Fish sex determination (SD) systems are varied, suggesting evolutionary changes including either multiple evolution origins of genetic SD from nongenetic systems (such as environmental SD) and/or turnover events replacing one genetic system by another. When genetic SD is found, cytological differentiation between the two members of the sex chromosome pair is often minor or undetectable. The turbot ( Scophthalmus maximus ), a valuable commercial flatfish, has a ZZ/ZW system and a major SD region on linkage group 5 (LG5), but there are also other minor genetic and environmental influences. We here report refined mapping of the turbot SD region, supported by comparative mapping with model fish species, to identify the turbot master SD gene. Six genes were located to the SD region, two of them associated with gonad development ( sox2 and dnajc19 ). All showed a high association with sex within families ( P = 0), but not at the population level, so they are probably partially sex-linked genes, but not SD gene itself. Analysis of crossovers in LG5 using two families confirmed a ZZ/ZW system in turbot and suggested a revised map position for the master gene. Genetic diversity and differentiation for 25 LG5 genetic markers showed no differences between males and females sampled from a wild population, suggesting a recent origin of the SD region in turbot. We also analyzed associations with markers of the most relevant sex-related linkage groups in brill ( S. rhombus ), a closely related species to turbot; the data suggest that an ancient XX/XY system in brill changed to a ZZ/ZW mechanism in turbot.